Factors affecting cycling life of LiNi0.8Co0.15Al0.05O2 for lithium-ion batteries. Issue 21 (11th May 2016) - Makimura, Yoshinari; Sasaki, Tsuyoshi; Nonaka, Takamasa; Nishimura, Yusaku F.; Uyama, Takeshi; Okuda, Chikaaki; Itou, Yuichi; Takeuchi, Yoji
Abstract : Factors affecting the cycling life of cylindrical lithium-ion batteries of LiNi0.8 Co0.15 Al0.05 O2 (NCA) with graphite were examined in terms of the rechargeable capacity and polarization of NCA derivatives of Li z Ni0.8 Co0.15 Al0.05 O2− δ (0.8 ≤ z ≤ 1.05). Abstract : Factors affecting the cycling life of cylindrical lithium-ion batteries of LiNi0.8 Co0.15 Al0.05 O2 (NCA) with graphite were examined in terms of the rechargeable capacity and polarization of NCA derivatives of Li z Ni0.8 Co0.15 Al0.05 O2− δ (0.8 ≤ z ≤ 1.05). NCA derivatives with rock-salt domains in the structure were prepared by a co-precipitation method and the structures of [Li1− y Ni y ] 3(b) [Ni, Co, Al] 3(a) O2 6(c) based on a space group of R 3̄ m were refined by a Rietveld method of the XRD patterns. The electrochemical reactivity of the NCA derivatives with rock-salt domains was examined in non-aqueous lithium cells, and it was found that the rechargeable capacities ( Q ) of the samples decrease linearly as the amount of rock-salt domain ( y ) increases. An empirical relation is obtained to be Q = 181.4 − 725.5 y in which Q reaches zero at y = 0.25, which is derived from not only the capacity loss owing to inactive rock-salt domains but also the polarization increase. The galvanostatic intermittent titration technique (GITT) measurement told us that polarization of NCA derivatives increases when the amount of rock-salt domains is above 2%, i.e., y > 0.02, and such a relation is remarkable in the lithium insertion direction into the structure, which is ascribed to slow lithium ion mobility due to nickel ions in the lithium layers. The NCA derivatives with increased rock-salt domains of above 2% deteriorate rapidly in non-aqueous lithium cells upon charge and discharge cycles, which is ascribed to the cumulative increase in polarization during charge and discharge. An extended cycling test for cylindrical lithium-ion batteries of the NCA derivatives with a graphite negative electrode at elevated temperature was performed and the quantitative relation is discussed thereof.